Promoting Students' Autonomous Learning Using Portfolio Assessment in EFL Writing Class - Tyas, Peptia Asrining (JEES (Journal of English Educators Society), 2020)
This study attempts to present the implementation of portfolio assessment to promote students’ autonomous learning in one of reputable universities in Indonesia. The participants were 30 students enrolled Essay Writing Class. A collection of students’ work during the course in the form of ‘Essay Writing Module’ was used to provide authentic evidence of the implementation of portfolio assessment and observation checklists of students’ work was used to present the completeness of portfolio assessment of each student. To know students’ autonomous learning, semi-structured interview was carried out. The results prove that portfolio assessment can promote students autonomous learning since it provides some benefits for students such as motivate them to do self-evaluation and reflection, encourage them to be actively involved in peer review session, and also enhance their awareness of their weaknesses. HIGHLIGHTS: Portfolio assessment promotes students’ autonomous learning by providing some benefits for students such as provide a guide for self-evaluation, reflection, and peer review. Each element in portfolio encourages students’ engagement during the writing activities both inside and outside the classroom. An insightful idea of specific criteria motivates students to set goals in improving their writing competence and performance.